Determination of the optimal resting period of the associated pasture Lolium multiflorum, Trifulium pratense and Medicago sativa, when grazed by guinea pigs in the central highlands of Peru - Mamani E., Ruth (2015)
The aim of the present study was to determine the optimal resting period of an associated pasture composed of Lolium multiflorum, Trifolium pratense and Medicago sativa to improve pasture productivity, live weight gain, feed conversion index and cost of production when is grazed by weaned genetically improved male guinea pigs. A randomized complete block design with two grazing cycles of 72 days as blocks and three treatments corresponding to resting periods of 22, 34 and 46 days in 36, 54 and 72 m² of grazing area and 2, 3 and 4 guinea pigs at grazing respectively was used. The results showed that resting periods between 22 to 46 days nor affect the yield of the associated pasture neither the economic parameters in guinea pigs reared under grazing.